Readiness Toward the Implementation of Open Science Initiatives In the Republic of Moldova - Țurcan Nelly; Cuciureanu Gheorghe; Cujba Rodica; Cojocanu Irina; Cojocaru Igor (Central European Journal of Public Policy, 2023)
Open Science paradigm involves transformations throughout the entire cycle of scientific research. Decision-makers play the key role of paradigm change facilitators. Consequently, the promotion of Open Science requires a political commitment.